The Effect Of TGT (Team Games Tournament) Learning Model Assisted By Crossword Puzzle Media For Learning Outcomes In Mathematics - Indah Silvia Nasir; Nurrohmatul Amaliyah (Green Publisher Indonesia, 2024)
Learning is an important aspect of education that influences individual quality. However, the lack of variety in teaching methods often results in low student learning outcomes, especially in Mathematics subjects at SDN Kapuk 11 Pagi. This research aims to determine the effect of the TGT (Team Games Tournament) type learning model assisted by crossword media on the mathematics learning outcomes of fourth grade elementary school students. Using a quantitative method with a quasi-experimental design, the sample consisted of 60 grade IV students who were divided into experimental and control groups. Data was collected through a written test and analyzed using the Independent Sample T-test. The research results show that the application of the TGT learning model using crossword puzzles significantly improves student learning outcomes. The average score of the experimental group students was 86.00, while the control group was 64.83. The t test shows the calculated t value of 9.49 is greater than the t table value of 2.003 with an effect size of 1.47 which indicates a high influence. In conclusion, the TGT type cooperative learning model assisted by crossword puzzles is effective in improving students' mathematics learning outcomes by increasing cooperation, motivation and skills, making learning more interesting and interactive. Teachers are encouraged to use this model effectively and vary their teaching methods to improve the quality of learning.